Impact of sourcing from the informal economy on the export likelihood and performance of emerging economy firms. (30th September 2021) - Escobar, Octavio; Lamotte, Olivier; Colovic, Ana; Meschi, Pierre-Xavier
Abstract: Building on the institutional economics perspective, we study how local firms in an emerging economy exploit institutional voids by sourcing inputs from industries with a large informal economy. We argue that this allows them to build a cost-related competitive advantage and leverage it both to export and to enhance export performance. The empirical study uses a unique dataset compiled by the Mexican authorities covering manufacturing plants between 2005 and 2012. Our results indicate that firms operating in industries that procure from industries with an extensive informal economy are more likely to export and to have better export performance.